2015
DOI: 10.1111/mcn.12202
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of e‐technologies in improving breastfeeding outcomes among perinatal women: a meta‐analysis

Abstract: A growing line of research has highlighted that e-technologies may play a promising role in improving breastfeeding outcomes. The objective of this review was to synthesise the best of available evidence by conducting a meta-analysis to evaluate whether e-technologies have had any effect in improving breastfeeding outcomes among perinatal women. The review was conducted using nine electronic databases to search for English-language research studies from 2007 to 2014. A 'risk of bias' table was used to assess m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 52 publications
2
64
1
4
Order By: Relevance
“…Web‐based education has become widespread thanks to the ease of accessibility, ability to provide continuous information support in the desired time and place, and the use of different methods (video, animation, etc. ; Lau, Htun, Tam, & Klainin‐Yobas, ). Nurses are expected to be able to use the developing technology while fulfilling their responsibilities related to the protection and promotion of maternal and infant health in antenatal and postnatal period (Kumar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Web‐based education has become widespread thanks to the ease of accessibility, ability to provide continuous information support in the desired time and place, and the use of different methods (video, animation, etc. ; Lau, Htun, Tam, & Klainin‐Yobas, ). Nurses are expected to be able to use the developing technology while fulfilling their responsibilities related to the protection and promotion of maternal and infant health in antenatal and postnatal period (Kumar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However we are unaware of any other studies reporting the outcomes of a mobile phone app targeting parents' healthy infant feeding practices. A recent meta-analysis of 16 studies in developed countries has shown e-technologies (including SMS, web, and interactive computer agent) to be effective in improving rates of breastfeeding initiation, duration and exclusivity [51]. This review however did not include any studies utilising a mobile phone app.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Evidence from systematic reviews and meta-analyses suggested moderate to strong positive effects of SMS interventions on disease prevention behaviors, particularly smoking cessation, physical activity, and weight loss [9][10][11][12] ; however, little evidence exists as to the effect of SMS interventions on BF behavior. Only 2 studies were published to date [13][14][15] and although both found positive effects of the intervention on EBF duration, there is a lack of high-quality, randomized, controlled trial (RCT) evidence testing the effectiveness of SMS interventions on BF behavior. The Lactation Advice Through Texting Can Help (LATCH) study was designed to address this gap.…”
Section: Evidence-based Text Messaging Interventionsmentioning
confidence: 99%